Answer:
the answer should be Annie
Approaching algebraicly(Take 2 as x)
(-x)^3-x^3
Simplify
Result is -2x^3
Put back 2
-2(2)^3 = -2(8)
= -16
<span> f(x) = x^2 + 4x − 1 and g(x) = 5x − 7
</span>(fg)(x) = (x^2 + 4x − 1)(5x − 7)
(fg)(x) = 5x^3 + 20x^2 - 5x - 7x^2 - 28x + 7
(fg)(x) = 5x^3 + 13x^2 - 33x + 7
answer is C. third choice
(fg)(x) = 5x^3 + 13x^2 - 33x + 7
Answer:
3077.2
Step-by-step explanation:
A circle's mass is found by
Pie times R^2
7^2 is 49, times 3.14 is 153.86
then you Multiply 153.86 by 20 which gives you 3077.2